An examination of student user experience (UX) and perceptions of remote invigilation during online assessment - Sefcik, Lesley; Veeran-Colton, Terisha; Baird, Michael; Price, Connie; Steyn, Steve (Australasian Society for Computers in Learning in Tertiary Education, 2022)
This study aimed to understand the effects of a custom-developed, artificial intelligence–based, asynchronous remote invigilation system on the student user experience. The study was conducted over 3 years at a large Australian university, and findings demonstrate that familiarity with the system over time improved student attitudes towards remote invigilation. Positive experiences were found to be related to ease of use and convenience for test sitting. The majority of students reported that it was important for the institution to have approaches such as remote invigilation to discourage cheating and they believed that the system was useful in this regard. Perceived technical problems were found to invoke feelings of anxiety with being remotely invigilated, and students suggested that greater clarity on expectations of appropriate behaviour, privacy and data security would help alleviate discomfort and improve the system.